How valid is your case formulation? Empirically testing your cognitive behavioural case formulation for tailored treatment. (20th July 2016) - Mumma, Gregory H.; Fluck, Jonathan
Abstract: Although clinicians have used cognitive behavioural case formulations (CBCFs) to guide treatment for many years, the validity of the case formulation (CF) is rarely evaluated. Given the central role of the formulation in treatment planning, particularly for complex or comorbid cases, a straightforward method to empirically evaluate the validity of the CBCF could increase the effectiveness of a treatment plan tailored for a particular client. This article describes a step-by-step, person-specific approach to evaluating a CBCF that can be used for appropriate cases in a clinical practice or especially a clinical training setting. The evaluation focuses on discriminant validity of person-specific scales and constructs and patterns of predicted functional relationships between idiosyncratic cognitions and distress. The approach is illustrated with an adult seen in a training clinic who was diagnosed with generalized anxiety and recurrent major depressive disorders and who completed 28 brief end-of-day, individualized questionnaires. The clinician's CBCF hypotheses were empirically evaluated using mostly simple statistical analyses available in readily accessible worksheets. Intervention implications of the CF evaluation are discussed.